2015
DOI: 10.1037/pas0000045
|View full text |Cite
|
Sign up to set email alerts
|

Two types of disengagement during couples’ conflicts: Withdrawal and passive immobility.

Abstract: A series of 3 studies using nonclinical samples investigated validity associated with the Conflict Disengagement Inventory (CDI), a questionnaire developed to measure passive immobility and withdrawal as context-specific forms of disengagement in couples' conflicts. In the first study, 2,588 married participants completed the CDI, and an expected 2-dimensional factor structure was confirmed. Additionally, results demonstrated measurement invariance across racial/ethnic and gender groups. In the second study, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Withdrawing can inhibit the individual from showing support to the other partner (Davila, Bradbury, Cohan, & Tochluk, 1997) and, because it compromises the individual's own recovery from the conflict, results in relationship dissatisfaction for both partners (Nichols, Backer-Fulghum, Boska, & Sanford, 2015). The poor post-conflict recoveries associated with a partner's withdrawal may also stem from the nonverbal messages that the withdrawing partner communicates to the other while withdrawn (Noller et al, 2005;Roberts, 2000).…”
Section: Withdrawal Following Conflict and Affective Recoverymentioning
confidence: 99%
“…Withdrawing can inhibit the individual from showing support to the other partner (Davila, Bradbury, Cohan, & Tochluk, 1997) and, because it compromises the individual's own recovery from the conflict, results in relationship dissatisfaction for both partners (Nichols, Backer-Fulghum, Boska, & Sanford, 2015). The poor post-conflict recoveries associated with a partner's withdrawal may also stem from the nonverbal messages that the withdrawing partner communicates to the other while withdrawn (Noller et al, 2005;Roberts, 2000).…”
Section: Withdrawal Following Conflict and Affective Recoverymentioning
confidence: 99%
“…While this may be due to the fact that the second study used a smaller sample and thereby had more error variance, it also may be due to the fact that the correlation between attributions and flat emotion was somewhat larger in the sample of dating people than the sample of married people. Previous research finds withdrawal from relationship is associated with flat emotion (Nichols et al, 2015), and thus, there may be reason to speculate that dating people are less committed and thereby more likely than married people to withdrawa from a relationship and experience flat emotion when they make blaming attributions. Taken together, the results suggest that there may be differences in attribution processes between marriage relationships and dating relationships; however, these ideas need to be tested directly before any firm conclusions can be made.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, if context-specific attributions are assessed across multiple episodes of conflict, multilevel modeling can be used to distinguish context-specific effects (which involve within-person variance) from schematic effects (which involve between-person variance). Other research on conflict in couples has used this approach and found that associations between variables involving the experience of emotions, communication behavior, conflict disengagement, the perception of partner emotions, and the experience of underlying concerns all occur at a context-specific level (Nichols et al, 2015;Sanford 2007aSanford , 2012Sanford & Grace, 2011). In sum, attributions may have important effects at the context-specific level, and the new context-specific attribution scale may be useful in future research testing these effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in order to maintain a sense of independence and control in the context of conflict with a partner, avoidantly attached individuals may refuse to engage in a conflict discussion, display an unwillingness to deal with their partner’s distress and needs, dismiss the importance of the issue, limit disclosure and openness, and create physical or psychological distance (Feeney & Karantzas, 2017; Nichols et al, 2015; Mikulincer & Shaver, 2003, 2016). Beyond the realm of conflict, individuals high on attachment avoidance also tend to emotionally disconnect from, and neglect their partner, as well as minimize their sense of responsibility toward their romantic partner (Mikulincer & Shaver, 2003, 2016).…”
Section: Insecure Attachment Orientations and Partner Maltreatmentmentioning
confidence: 99%